Bone mineral density at distal forearm in men over 40 years of age in Mae Chaem district, Chiang Mai Province, Thailand: a pilot study - Montree Tungjai (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Objective: To study the prevalence of bone mineral density (BMD) and osteoporosis in the distal forearm among Thai men over 40 years of age in Mae Chaem District, Chiang Mai Province, Thailand. Methods: The subjects in this study were 194 Thai men, aged between 40 and 87 years who resided in Mae Chaem District, Chiang Mai Province, Thailand. Self-administered questionnaires were used for receiving the demographic characteristics information. BMD was measured by peripheral dual energy X-ray absorptiometry at the nondominant distal forearm in all men. Results: The BMD was highest in the age-group 40–49 years and lowest in the age-group 70–87 years. The average T-score at the distal forearm was also highest in the age-group 40–49 years and lowest in the age-group 70–87 years. The BMD decreased as a function of age-group (p <.05). In contrast, the BMD increased as a function of weight (p <.05). Height had weak impact on the BMD in the distal forearm (p >.05). The percentage of osteopenia and osteoporosis are increased as a function of age-group in, while decreased in that of normal bone density. Conclusions: We found the prevalence of osteoporosis in men who resided in Mae Chaem District, Chiang Mai Province, Thailand.